Terrorism-induced uncertainty and firm R&D investment: A real options view - Li, Daitian; Tong, Tony W; Xiao, Yangao; Zhang, Feida (Journal of International Business Studies, 2022)
How terrorism affects firms’ investment decisions is gaining increasing attention globally and represents a frontier topic in international business. Although extant research has shown that terrorism can reduce aggregate investment levels, little attention has been paid to the impact of terrorism on firms’ R&D in a global context. Drawing on real options theory, we argue that terrorism will lead firms to reduce their R&D investment because terrorism-induced uncertainty increases the value of the deferral option in R&D. However, strong national institutions, including strong patent rights protection and low expropriation hazards, will mitigate firms’ disincentive to invest in R&D stemming from uncertainty. Further, multinational firms, larger firms, as well as firms with greater cash flow will be less sensitive to uncertainty in their R&D decisions. Our hypotheses are supported by a battery of tests, including the use of a quasi-experiment, based on firm-level panel data from 48 countries.